A study of bearings for wind turbine application - Yiew, Mindy Yu Rong (2014)
For the past few decades, ball bearings had been commercially produced and had dominated the market. But however, ball bearings can wear out easily and have a definite life. High loads and speed are usually needed for wind turbine application; hence, the solution is to employ the use of hydrodynamic bearing as it is able to support greater loads and speed. Additionally, it does not have a definite life unlike that of a ball bearing. On the hindsight, hydrodynamic bearings are not as common as ball bearings and are usually tailored for the user’s application. Therefore, they are not commercially mass produced and are not easily available on the market. Design parameters such as design loads, rotational speed, length and diameter of bearing, and selection of an appropriate lubrication need to be set up first. After which, numerical analysis of the design was carried out to determine the frictional force and actual load carrying force. Alternatively, analytical analysis (Somerfield analysis) can also be used to calculate the same properties. In this report, both ways were analyzed and produced the same result. The actual prototype was manufactured after the results from the numerical or analytical analysis were satisfactory. An experiment was set up to and the designed load of the prototype was able to carry loads at values close to the designed carrying capacity without failing prematurely. The same experiment was also used to determine the frictional losses of the system, which was then compared to the calculated friction for further analysis.